2021
DOI: 10.3390/nu13082650
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Nutritional Aspects of Plant-Based Beverages Used as Substitutes for Cow’s Milk

Abstract: The presence of milk in meals and products consumed daily is common and at the same time the adoption of a milk-free diet increases due to milk allergy, lactose intolerance, vegan diets, and others. Therefore, there is an increasing demand for plant-based beverages, which present variable and, sometimes, unknown nutritional characteristics. This study sought to compare the nutritional aspects of plant-based beverages used as substitutes for cow’s milk described in scientific studies. Therefore, we used a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 38 publications
5
78
0
2
Order By: Relevance
“…In general, the demand for plant-based beverages has increased throughout the world in the last years [ 330 , 331 , 332 ] and can be divided into five categories: cereal-based (oat, rice, corn, spelt), legumes-based (soy, peanut, lupin, cowpea, chickpea), nut-based (almond, coconut, cashew, hazelnut, Brazil nut, pistachio), seed-based (sunflower, sesame, hemp), and pseudocereal-based (quinoa, teff, amaranth) beverages [ 10 , 144 , 333 , 334 , 335 ]. It has been reported that parents and caretakers are increasingly feeding infants and young children with such plant-based beverages as alternatives to cow’s milk-based products, including as substitutes for cow’s milk-based infant formulas [ 336 , 337 ].…”
Section: Plant-based Infant Formulasmentioning
confidence: 99%
“…In general, the demand for plant-based beverages has increased throughout the world in the last years [ 330 , 331 , 332 ] and can be divided into five categories: cereal-based (oat, rice, corn, spelt), legumes-based (soy, peanut, lupin, cowpea, chickpea), nut-based (almond, coconut, cashew, hazelnut, Brazil nut, pistachio), seed-based (sunflower, sesame, hemp), and pseudocereal-based (quinoa, teff, amaranth) beverages [ 10 , 144 , 333 , 334 , 335 ]. It has been reported that parents and caretakers are increasingly feeding infants and young children with such plant-based beverages as alternatives to cow’s milk-based products, including as substitutes for cow’s milk-based infant formulas [ 336 , 337 ].…”
Section: Plant-based Infant Formulasmentioning
confidence: 99%
“…Nevertheless, in most cases they are high in carbohydrates and low in protein, containing up to 30 times less protein than cow's milk. Soy beverages have the most similar protein content to cow's milk [16,141]. Even so, vegetable protein is inferior, mainly due to the presence of limiting amino acids (lysine in cereals, methionine in legumes) and poor digestibility [127,129].…”
Section: Fermentation Of Legumes Using Labmentioning
confidence: 99%
“…Compared to milk, plant-based beverages have a low content of saturated fatty acids (less than 0.7 g/100 g), with the exception of coconut beverage, which is SFA-rich (about 1.7 g/100 g) [137]. Plant-based beverages are dominated by unsaturated fatty acids, mainly in the form of oleic, linolenic, and linoleic acids [127,137,141]. Cow's milk is a natural source of calcium (120 mg/100 g on average), and plant-based beverages tend to be low in this nutrient if not fortified during production.…”
Section: Fermentation Of Legumes Using Labmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing interest in plant-based alternatives due to allergies, intolerance, or for perceived health benefits or cultural values, which are leading some families to feed their babies plant-based “milks” that are not designed specifically for infant or young children and are deficient in nutrients [ 16 , 17 ]. Although certain nuts can be allergenic for some individuals and their use should be evaluated with caution for allergic individuals [ 18 ], the common protein sources in infant formulas, cow milk and soy, are major allergens. Moreover, recent guidelines recommend the early introduction of allergens to infants below the age of 12 months [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%